Illness and health care in ancient Israel : the role of the social-cultural context in interpreting 2 Chronicles 26:11-23 - Prinsloo, G.T.M. (Gert Thomas Marthinus) (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 2008.